Effect of the bacillus of Calmette-Guerin, Propionibacterium acnes and avridine as immunomodulators in antirabies vaccination of mice using the Fuenzalida-Palacios mouse brain vaccine - Megid, Jane [UNESP]; Peracolli, MTS; Curi, P. R.; Zanetti, C. R.; Cabrera, M. H.; Vassao, R.; Ito, F. H. (Elsevier B.V., 1999)
Using the laboratory mice, Fuenzalida-Palacios mouse brain human rabies vaccine was administered in groups of animals previously inoculated with rabies virus and then submitted to treatments with the immunomodulators onco-BCG, avridine and Plopionibacterium acnes. Humoral and cellular immune responses were evaluated through the macrophage inhibition factor (MIF), intra-pad inoculation (IPI) and serum neutralization (SN) tests and by the detection of gamma-interferon (IFN-gamma). The IPI test was not effective in detecting the response of delayed-type hypersensitivity, contrary to MIF, which showed the immune cellular response. Higher levels of IFN-gamma were observed in the groups of mice vaccinated and treated with avridine and P. acnes. Although immunomodulating activities have been detected, the use of adjuvants with the Fuenzalida-Palacios type vaccine in mice did not reveal any encouraging results. (C) 1999 Elsevier B.V. Ltd. All rights reserved.
Keywords: rabies; vaccination; immunomodulators; mice; immunity